2009
DOI: 10.1021/jp905580j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight into the Inhibition Effect of Trehalose on the Nucleation and Elongation of Amyloid β-Peptide Oligomers

Abstract: Soluble amyloid oligomers are a cytotoxic species in Alzheimer's disease, and the recent discovery that trehalose can prohibit aggregation of amyloid beta-peptide (Abeta) has received great attention. However, its inhibition mechanism remains unclear. In order to investigate the molecular mechanism of the inhibition effect, molecular dynamics simulations of Abeta(16-22) and Abeta(40) peptides at different trehalose concentrations (0-0.18 mol/L) are performed using an all-atom model. The simulations confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
74
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 55 publications
(119 reference statements)
4
74
0
1
Order By: Relevance
“…It is at the concave edge that new peptides would attach in the unidirectional growth model of the Aβ fibril. Ibuprofen formed clusters within the groove of the concave edge, precluding the attachment of additional Aβ peptides, a hypothesis confirmed by Chang et al 114 The authors further observed that interactions between ibuprofen and the peptide side chains 102 and model parallel β-strands (right) similar to those considered by Convertino et al 99 The parallel β-sheet structure is also used to illustrate the approximate binding sites of the indicated molecules to antiparallel β-sheet models considered by Viet et al 65 and Liu et al 101 were principally responsible for the ibuprofen−Aβ interaction, with few contacts formed involving Aβ backbone groups. Takeda et al performed very similar simulations with naproxen, 112 finding that, like ibuprofen, naproxen bound to the concave edge of the Aβ 10−40 fibril in order to preclude the attachment of other Aβ peptides.…”
Section: Molecular Dynamics Simulations Of Full-length Aβmentioning
confidence: 73%
See 3 more Smart Citations
“…It is at the concave edge that new peptides would attach in the unidirectional growth model of the Aβ fibril. Ibuprofen formed clusters within the groove of the concave edge, precluding the attachment of additional Aβ peptides, a hypothesis confirmed by Chang et al 114 The authors further observed that interactions between ibuprofen and the peptide side chains 102 and model parallel β-strands (right) similar to those considered by Convertino et al 99 The parallel β-sheet structure is also used to illustrate the approximate binding sites of the indicated molecules to antiparallel β-sheet models considered by Viet et al 65 and Liu et al 101 were principally responsible for the ibuprofen−Aβ interaction, with few contacts formed involving Aβ backbone groups. Takeda et al performed very similar simulations with naproxen, 112 finding that, like ibuprofen, naproxen bound to the concave edge of the Aβ 10−40 fibril in order to preclude the attachment of other Aβ peptides.…”
Section: Molecular Dynamics Simulations Of Full-length Aβmentioning
confidence: 73%
“…Though the solvent is often viewed as a passive entity in most simulations, several studies have shown that water-mediated interactions may play a significant role in Aβ aggregate stability 120 and the interactions of Aβ with small molecules. 101,110 Several other studies summarized here employed implicit solvent representation, 99,100,111−114 though it is unclear what, if any, effects can be attributed to the absence of explicit water molecules. The other technique used to reduce the degrees of freedom in the system is the application of coarse-grained force fields, which have been utilized in several studies of Aβ dynamics.…”
Section: Molecular Dynamics Simulations Of Full-length Aβmentioning
confidence: 98%
See 2 more Smart Citations
“…These explanations are consistent with molecular dynamics simulations which showed that preferential exclusion of trehalose is the origin of its inhibition of Aβ40 aggregation, partly due to stabilization of monomers with -helical structure so that β-sheet structure is prevented. 59 Compounds that retard Aβ aggregation by stabilizing helical structure may be of therapeutic benefit in AD because nascent Aβ generated by -secretase cleavage of transmembrane protein C99 (APP 672-770 , also called -CTF) is likely to comprise substantial helical content, since residues 17-23 of Aβ arise from the C99 "N-helix" (APP 688-694 ) and residues 29-40/42 of Aβ (APP 700-711/713 ) originate from within the C99 helical transmembrane domain (APP 700-723 ). 60 The effect of trehalose glycocluster 10 on Aβ40-induced neurotoxicity was studied using a cell-based trypan blue dye exclusion assay.…”
mentioning
confidence: 99%